2014
DOI: 10.1039/c3ra45444d
|View full text |Cite
|
Sign up to set email alerts
|

Thiaporphyrins: from building blocks to multiporphyrin arrays

Abstract: Thiaporphyrins and 21,23-dithiaporphyrins resulting from the replacement of one and two pyrrole rings respectively, of tetrapyrrolic porphyrins possess singlet state energy levels which are lower than porphyrins and metalloporphyrins. This specific feature of thiaporphyrins is advantageous when thiaporphyrins are connected either covalently or non-covalently to porphyrins and metalloporphyrins for unidirectional flow of energy transfer/electron transfer. In recent times, the synthetic routes were developed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…The core-modified porphyrins or heteroporphyrins possess very interesting physicochemical properties that are quite different from regular tetrapyrrolic porphyrins . Several covalently and noncovalently linked heteroporphyrin-based multiporphyrin arrays were synthesized, and their properties were explored . New heterocorroles, heterocalix[4]­phyrins, and metal derivatives of heteroporphyrins were synthesized and characterized. , During our course of investigations, we realized that the reports on the heterobenziporphyrins, which are a subclass of benziporphyrins in which one of the pyrrole rings is replaced with other heterocycles such as thiophene, furan, etc., are very few. , Lash and co-workers reported the first synthesis of nonaromatic heterobenziporphyrins in which one of the pyrrole rings was replaced either by thiophene Ia or furan Ib (Chart ).…”
Section: Introductionmentioning
confidence: 99%
“…The core-modified porphyrins or heteroporphyrins possess very interesting physicochemical properties that are quite different from regular tetrapyrrolic porphyrins . Several covalently and noncovalently linked heteroporphyrin-based multiporphyrin arrays were synthesized, and their properties were explored . New heterocorroles, heterocalix[4]­phyrins, and metal derivatives of heteroporphyrins were synthesized and characterized. , During our course of investigations, we realized that the reports on the heterobenziporphyrins, which are a subclass of benziporphyrins in which one of the pyrrole rings is replaced with other heterocycles such as thiophene, furan, etc., are very few. , Lash and co-workers reported the first synthesis of nonaromatic heterobenziporphyrins in which one of the pyrrole rings was replaced either by thiophene Ia or furan Ib (Chart ).…”
Section: Introductionmentioning
confidence: 99%
“…60,62,63 Cu-catalyzed Huisgen 1,3-dipolar cycloaddition between azide-and acetylene-containing derivatives is the most effective reaction of this type which has led to a variety of porphyrin, phthalocyanine and other chromophore containing systems. [64][65][66][67][68][69][70] The 1,2,3-triazole bridge that results from such reactions has been proven to be very efficient for energy transfer in donor-acceptor systems. 71,72 Also, according to literature reports, the measured efficiencies for a variety of mono-carboxylphenyl triaryl porphyrins have shown values from 0.5 to 3% in standard DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…may lead to core-modified calixphyrins which may exhibit interesting electronic and structural features that differ from calixphyrins. 17,18 A few years back, we reported thiacalixphyrins 19,20 1 and 2 (Chart 1) containing one or two thiophene sulfur(s) in place of pyrrole nitrogen(s) and showed that the thiacalixphyrin properties were quite novel and different from those of thiaporphyrins. In thiacalixphyrins 1 and 2, the thiophene(s) and pyrroles were connected by one sp 3 -and three sp 2 meso-carbon bridges (Chart 1).…”
Section: Introductionmentioning
confidence: 99%